(untitled) (Global Journal of Science Frontier Research, 2022)
The continuous growing worlds impact of climate change global warming including frequent natural disasters such as earthquakes wildfires etc rising food insecurity infectious diseases etc among others causing economic political and civil unrest cannot be downplayed Carbon dioxide CO2 is the most significant contributor to climate change mainly generate through human-induced industrial and techno logical advancement activities Africa is most vulnerable to the impact of climate change in the world Hence any effort to combat climate change in Africa will be an outstanding achievement towards mitigating the excessive effect of climate change globally We proposed a surface response optimization method to optimize mini mize the CO2 emissions in Africa We utilized the desirability function approach to obtain the optimum value of the risk factors that minimize Africa s CO2 emissions The minimum value of the CO2 was obtained along with a 95 confidence region Also the bivariate interaction effect of the risk factors on the CO2 was obtained The optimization process is well-validated to satisfies the necessary conditions achieving a desirability function of 0 99 The proposed method provides a robust mitigating approach towards combating CO2 emission limiting the impact of climate change in Africa and its impact on the world The subject of essential findings is based on the very high quality of a predictive real data-driven statistical model developed by the authors that identify the significant risk factors and interactions that produce CO2 emissions in the atmosphere